2022
DOI: 10.7150/ijbs.75410
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation in Cancer: From the Impacts and Mechanisms to Treatment potentials

Abstract: Cancer is a public health problem of great concern, and it is also one of the main causes of death in the world. Cancer is a disease characterized by dysregulation of diverse cellular processes, including avoiding growth inhibitory factors, avoiding immune damage and promoting metastasis, etc. However, the precise mechanism of tumorigenesis and tumor progression still needs to be further elucidated. Formations of liquid-liquid phase separation (LLPS) condensates are a common strategy for cells to achieve diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 237 publications
(282 reference statements)
0
14
0
Order By: Relevance
“…Mechanics has a further role in cellular organisation, for example in phase separation. Phase separation is the process responsible for cellular compartmentalization, involving the assembly of condensates which are membraneless organelles such as stress granules and polycomb bodies (18). Dysregulated components in cancer can affect the location and the regulation of condensates, thereby leading to altered gene expression (19).…”
Section: The Role Of Cell Morphology and Microarchitecturementioning
confidence: 99%
“…Mechanics has a further role in cellular organisation, for example in phase separation. Phase separation is the process responsible for cellular compartmentalization, involving the assembly of condensates which are membraneless organelles such as stress granules and polycomb bodies (18). Dysregulated components in cancer can affect the location and the regulation of condensates, thereby leading to altered gene expression (19).…”
Section: The Role Of Cell Morphology and Microarchitecturementioning
confidence: 99%
“…The disheveled binding antagonist of -catenin 1 (DACT1), a target gene of transforming growth factor (TGF-), can assemble BMCs within the cytoplasm that sequester casein kinase 2 (CK2) and prevent WNT signaling. Thus, DACT1 BMCs play a vital role in the metastatic process of breast and prostate cancer cells [ 33 , 34 ]. IDRs within the signalosome scaffold protein Dishevelled 2 (Dvl2) mediate LLPS.…”
Section: Misregulated Signaling and Transductionmentioning
confidence: 99%
“…Because the molecules near the droplet's surface are more unstable than the molecular energy inside the droplet, when two droplets of similar size contact each other, the surface free energy is driven and will spontaneously fuse into larger droplets. This active aggregation was mediated by microtubules in stress granules (SGS), microtubules in the processing body (P-body), and motor proteins [ 32 , 33 ]. Alberti et al demonstrated through in vivo imaging and fluorescent labeling of P-body that these particles have liquid properties and can not only fuse, split, and change in size but also reversibly.…”
Section: Mechanism Of Phase Separation In Degenerative Diseasesmentioning
confidence: 99%